A pilot study of attachment style and emotional experience in adolescent girls with loss of control eating. (1st September 2016) - Ranzenhofer, Lisa M.; Engel, Scott G.; Crosby, Ross D.; Haigney, Mark; Tanofsky-Kraff, Marian
ABSTRACT: The established link between attachment insecurity and disinhibited eating may in part be explained by social problems, negative mood, and/or physiologic 'stress'; however, these mechanisms have not been tested in adolescents with loss of control (LOC) eating. We therefore examined associations among attachment styles, social problems, negative emotions, and autonomic indices in 32 adolescent girls with recurrent LOC eating (body mass index z-score = 2.2 ± 0.4; age = 14.9 ± 1.6 years). Participants completed the Behavioral Systems Questionnaire to assess relational styles (secure, preoccupied, avoidant) and the Beck Depression Inventory to assess depressive symptoms. Parents completed the Child Behavior Checklist to assess teen social problems. Ecological momentary assessment (EMA) of real-world negative affect and social problems was collected for two weeks, and ambulatory monitoring of autonomic indices for two days. Preoccupied attachment was positively associated with depressive symptoms ( n = 32, p = .03), greater EMA negative affect ( n = 29, p = .03), and marginally higher EMA social problems ( p = .06) . Further, avoidant attachment was positively associated with ambulatory heart rate ( n = 18, p < .05), but was not associated with any self-report indices. Adolescent girls with preoccupied versus dismissing attachment may exhibit different patterns of social problems, negative mood, and physiologic 'stress', suggesting the need for more detailed investigations of the mechanisms responsible for the relationship between insecure attachment and LOC eating.